Detection of Insulin in Insulin-Deficient Islets of Patients with Type 1 Diabetes - Yuliya Krivova; Alexandra Proshchina; Dmitry Otlyga; Anastasia Kharlamova; Sergey Saveliev (Life)
Type 1 diabetes (T1D) is related to the autoimmune destruction of β-cells, leading to their almost complete absence in patients with longstanding T1D. However, endogenous insulin secretion persists in such patients as evidenced by the measurement of plasma C-peptide. Recently, a low level of insulin has been found in non-β islet cells of patients with longstanding T1D, indicating that other islet cell types may contribute to persistent insulin secretion. The present study aimed to test the ability of various antibodies to detect insulin in insulin-deficient islets of T1D patients. Pancreatic autopsies from two children with recent-onset T1D, two adults with longstanding T1D, and three control subjects were examined using double immunofluorescent labeling with antibodies to insulin, glucagon and somatostatin. Immunoreactivity to insulin in glucagon+ cells of insulin-deficient islets was revealed using polyclonal antibodies and monoclonal antibodies simultaneously recognizing insulin and proinsulin. Along with this, immunoreactivity to insulin was observed in the majority of glucagon+ cells of insulin-containing islets of control subjects and children with recent-onset T1D. These results suggest that islet α-cells may contain insulin and/or other insulin-like proteins (proinsulin, C-peptide). Future studies are needed to evaluate the role of α-cells in insulin secretion and diabetes pathogenesis.